CRAFT (Cerclage after full dilatation caesarean section): protocol of a mixed methods study investigating the role of previous in-labour caesarean section in preterm birth risk - Carlisle, Naomi; Glazewska-Hallin, Agnieszka; Story, Lisa; Carter, Jenny; Seed, Paul T.; Suff, Natalie; Giblin, Lucie; Hutter, Jana; Napolitano, Raffaele; Rutherford, Mary; Alexander, Daniel C.; Simpson, Nigel; et al. (BMC Pregnancy and Childbirth, 2020)
Background: Full dilatation caesarean sections are associated with recurrent early spontaneous preterm birth and late miscarriage. The risk following first stage caesarean sections, are less well defined, but appears to be increased in late-first stage of labour. The mechanism for this increased risk of late miscarriage and early spontaneous preterm birth in these women is unknown and there are uncertainties with regards to clinical management. Current predictive models of preterm birth (based on transvaginal ultrasound and quantitative fetal fibronectin) have not been validated in these women and it is unknown whether the threshold to define a short cervix (≤25 mm) is reliable in predicting the risk of preterm birth. In addition the efficacy of standard treatments or whether benefit may be derived from prophylactic interventions such as a cervical cerclage is unknown. Methods: There are three distinct components to the CRAFT project (CRAFT-OBS, CRAFT-RCT and CRAFT-IMG). CRAFT-OBS: Observational Study; To evaluate subsequent pregnancy risk of preterm birth in women with a prior caesarean section in established labour. This prospective study of cervical length and quantitative fetal fibronectin data will establish a predictive model of preterm birth. CRAFT-RCT: Randomised controlled trial arm; To assess treatment for short cervix in women at high risk of preterm birth following a fully dilated caesarean section. CRAFT-IMG: Imaging sub-study; To evaluate the use of MRI and transvaginal ultrasound imaging of micro and macrostructural cervical features which may predispose to preterm birth in women with a previous fully dilated caesarean section, such as scar position and niche. Discussion: The CRAFT project will quantify the risk of preterm birth or late miscarriage in women with previous in-labour caesarean section, define the best management and shed light on pathological mechanisms so as to improve the care we offer to women and their babies. Trial registration: CRAFT was prospectively registered on 25th November 2019 with the ISRCTN registry (https://doi.org/10.1186/ISRCTN15068651).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Caesarean section; Cervix; Delivery; Full dilatation; Fully dilated; Labour caesarean; Late miscarriage; Preterm birth